Students Disclosing Disability and its Impact on their Educational Experiences in Higher Educational Institutions - Ambati, Nageswara Rao (JOURNAL OF INDIAN EDUCATION, 2017)
This study attempts to understand the factors that influence Students With Disabilities (SWDs) to disclose their disabilities and special needs and strategies adopted by them to manage their higher educational experiences. The study is exploratory in nature. To answer the research questions posed in this study, the researcher has used mixed methods. Three universities were selected through purposive sampling, so as to gain maximum diverse variation. For this study, in-depth interviews were conducted with a hundred SWDs in the selected universities in Andhra Pradesh, India. These findings of the study also emphasised how students took responsibility, understood the term disability, developed support systems, and disclosed their special needs to seek out services to overcome academic, as well as physical, barriers. This, in turn, helped in improving their educational experiences in higher education institutions and to pursue higher education successfully.